One-Year Course of Olanzapine-Induced Diabetic Ketoacidosis: A Case Report - Mohammed Zain Ulabedin Adhoni; Roomiyah Riyaz Assadi; Saira Abbas (Dubai Diabetes and Endocrinology Journal)
Second-generation antipsychotics, despite being highly effective, are among the drugs known to cause insulin resistance and metabolic syndrome, eventually leading to diabetes mellitus and less commonly diabetic ketoacidosis (DKA). Here, we present the case of a 21-year-old male, who was not previously known to have any comorbid factors but presented with DKA 1 year and 9 months after beginning treatment with olanzapine for an unspecified psychotic disorder requiring hospital admission and the resolution of the same following discontinuation of the drug. Our case report emphasizes the need for regular screening of patients requiring diabetogenic drugs, so that early identification of possible side effects can be noted and averted.